Lipid Profile in HIV Infected Children Receiving Antiretroviral Treatment - Lall, Dr. Kavita J.; Khurana, Dr. Omesh; Ambad, Dr. Ranjit S (International Journal of Innovative Research in Medical Science, 2018)
This study reviewed the lipid profile of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) patients in relation to use of antiretroviral therapy (ART). Lipid profile is becoming one of the common problems in human immunodeficiency virus infected patients receiving antiretroviral therapy. Data on lipid profile derangements induced by antiretroviral treatment. The aim of this study was to assess the lipid profile abnormalities in HIV infected children receiving ART. Material and Method - Information on sex, age, specific ART type in use , ART start date, duration of treatment, duration of HIV infection, BMI, relevant signs and symptoms and medications if any were collected by trained nurses using structured questionnaires and patients medical record. Blood Sample Collection, Transport and Processing - Following a standard and safety collection procedure, about 5 ml fasting venous blood was taken from the patients and the control groups by clinical nurses and senior laboratory technologist. Fasting serum samples were analyzed for total cholesterol (TC), triglyceride (TG), High Density Lipoprotein- Cholesterol (HDL-c). Low density lipoprotein cholesterol (LDL) and Very low density lipoprotein (VLDL) was determined by Friedewald Equation (13). Result and conclusion - There was statistically significant difference between the two groups for TC, TG, TC/HDL-c ratio and TG/HDL –c ratio. On the basis of our study we concluded that the level of TG, TC, HDL-c and VLDL-c is high in HIV positive populations receiving first line ART (group I) as compared to ART naïve (group II). Considering that these altered lipid profiles can be an independent risk factors for coronary artery diseases and myocardial infarction, treatment with first-line ART may actually have potential risks for cardiovascular health of HIV positive people receiving ART.